2011
DOI: 10.3116/16091833/12/2/62/2011
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical propagation of high-order elliptic vortex beams in a uniaxially anisotropic medium

Abstract: We have analysed propagation of nonparaxial and paraxial beams perpendicular to the optic axis in a uniaxially anisotropic medium (unbounded optically uniaxial crystal). We have presented the paraxial solutions in the form of generalised Hermite-Gaussian beams propagating perpendicular to the optic axis in a uniaxially anisotropic medium. We have also constructed the generalised Laguerre-Gaussian beams at the z=0 plane and analysed their evolution in a homogeneous isotropic medium. Comparing it with the evolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the present paper we focus our attention on the experimentally studied structural transformations of the elliptical vortex beams propagating perpendicular to the crystal optical axis. In the theoretical aspect it was found that solutions for the paraxial wave equation can be expressed in the form of the generalized Laguerre-Gaussian beams bearing high-order optical vortices [8]. Article contains two sections: the second chapter is devoted to theoretical explanation of sign-conversation phenomenon in uniaxial crystal; in the third section the results of experimental observation are displayed.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper we focus our attention on the experimentally studied structural transformations of the elliptical vortex beams propagating perpendicular to the crystal optical axis. In the theoretical aspect it was found that solutions for the paraxial wave equation can be expressed in the form of the generalized Laguerre-Gaussian beams bearing high-order optical vortices [8]. Article contains two sections: the second chapter is devoted to theoretical explanation of sign-conversation phenomenon in uniaxial crystal; in the third section the results of experimental observation are displayed.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that conversion of the elliptical singular beams has periodical features taking place along the beam axis z propagating along the perpendicular to the crystal optical axis [2]. The most interesting case springs up when the beam propagates nearly perpendicular to the optical axis with the deviation angle 7º so that 0 0 sin    .…”
Section: Experimental Study Of the Spin-orbital Couplingmentioning
confidence: 99%
“…In case the beam bears the optical vortex then the crystal changes the singular structure of the vortex. The slight changes of the crystal parameters can result in the critical transformations of the phase singularity [2][3][4]. However the question of the vortex generation in this case remains open.…”
Section: Introductionmentioning
confidence: 99%
“…2(a)). The effective beam can be approximately modelled with an elliptical Gaussian beam envelope covering a non-canonical vortex [30] (i.e. is not singular, but has a geometry and evolves continuously in z ).…”
mentioning
confidence: 99%